Towards a Strategic Internship Ecosystem: Collaboration-Based Internship Model for Bali’s Tourism Education - Bangun Mulia, Victor; Syamsul Alam Paturusi; I Wayan Suardana; I Nyoman Sukma Arida (Jurnal Internasional Riset Bisnis Pariwisata, 2025)
The research aimed at developing new structured internship model for tourism vocational schools in Bali as the current internship was lacking organized internship journey due to the absence of structured training plan. This was qualitative research in which data were collected through interviews with 21 informants from hospitality industries in Badung Regency and three representative of tourism vocational schools in Bai. Data were analyzed qualitatively as well. The research developed a New Internship Model consisting of eight stages; partnership, students pre- assessment, pre-placement, initiation, working, monitoring, termination, and feedback & evaluation. The model is a refinement of Kisser (2011) model which is only focused on five stages. Through structured stages, from preparation to final evaluation, this model helps students gain practical experience tailored to the needs of the tourism industry.